Safety of prolonged use of metoclopramide and domperidone as treatment for chronic gastrointestinal dysmotility disorders in patients with systemic sclerosis - Saad Alkhowaiter; Maha M. Al Rasheed; Nuha Alammar; Ammar Alotaibi; Mansour Altuwaijri; Suliman Alshankiti; Mohammed A. Omair; Majid Alsahafi (Elsevier, 2024)
Background: Metoclopramide and domperidone are prokinetic agents commonly used to treat gastrointestinal dysmotility disorders. This study aimed to evaluate the safety and associated side effects of prolonged-use metoclopramide and domperidone as treatment for chronic gastrointestinal dysmotility disorders in patients with systemic sclerosis (SSc). Methods: A quantitative observational survey was conducted by interview questionnaire in rheumatology outpatients at a tertiary teaching hospital in Riyadh, Saudi Arabia. The study included all patients aged 25-80 years diagnosed with SSc. All patients were on metoclopramide or domperidone for the treatment of chronic gastrointestinal dysmotility symptoms over at least 12 weeks. Results: Eighteen eligible patients were included. Most study participants were diagnosed with SSc complicated by interstitial lung disease (n = 13; 72.2 %). The most frequently reported side effect that occurred while taking prokinetic drugs was shortness of breath (n = 12; 66.7 %). None of the participants reported experiencing depression, galactorrhea, or syncope. CNS side effects were reported in 5.6 %. There were no differences in side effects based on the type and dosage of prokinetic drug used. Conclusions: Use of metoclopramide and domperidone for the treatment of chronic gastrointestinal dysmotility in SSc patients for 12 weeks or longer was not associated with any troublesome side effects. Further studies with more participants are needed to confirm our findings.